When religion meets culture: Inside Muhammadiyah’s "cultural da'wah study" on TvMu - Rifai, Ahmad; Rahman, Mohammad (Hanifiya: Jurnal Studi Agama-Agama, 2025)
This research examines the intersection of religion and culture within Muhammadiyah, specifically through the "Pengkajian Dakwah Kultural" [cultural da’wah study] program broadcasted on YouTube's TvMu. The study aims to explore how Muhammadiyah uses digital media to promote cultural da'wah while maintaining its religious integrity. Using a qualitative approach with narrative analysis, the study analyzes the content of TvMu's programs from 2021 to 2024, including dialogues, sermons, and cultural performances. The findings suggest that Muhammadiyah has embraced a more inclusive and adaptive approach to cultural integration, seeing culture not as a threat but as an integral part of its da'wah. The study reveals that digital media, particularly YouTube, plays a vital role in facilitating this integration, making religious teachings more accessible and relevant to a younger, tech-savvy audience. The research underscores the importance of balancing cultural authenticity with religious principles in the context of modern-day da'wah.